A Study to Assess the Postoperative Nursing Care in Orotta Medical Surgical National Referral Hospital from March - June 2013 Asmara, Eritrea. - Dr. Kavitha. P, (International Journal of Allied Medical Sciences and Clinical Research, 2020)
In the postoperative period, considerable effort is directed toward anticipation and prevention of problems. Patients undergoing surgery expected to have high quality of health care, and nurses play a significant role in the process together with other health care providers. The Aim and objectives Of the study were: to assess the postoperative nursing care, demographic variables and equipment' check list in Orotta national referral hospital, Asmara. Method The research design was, descriptive cross sectional study design, 35 staff members of surgical wards have been collected as samples by convenience sampling technique. The data was collected by using structured self administered questionnaire and observational check list. Collected data has been analyzed with the help of SPSS software. The postoperative nursing care was assessed in five aspects such as: vital signs, positioning & ambulation, fluid balance, pain & wound care and health education regarding nutritional & discharge advice and psychological support management. Results The results showed that the majority of the samples (74.3%) were rated in the moderately adequate level of knowledge on practice of postoperative nursing care that they deliver for their patients during their nursing care practicing while some (22.9%) were rated in the adequate level of knowledge on practice and few (2.9%) were rated in an inadequate level of knowledge on practice Conclusion There were less short comings in the nursing care that can be improved by continuous training and courses and in the observational check list of equipment’s even though most are available, adequate & working in good condition there is some limitation. In order to improve the quality of nursing care given to the post operative patients, some recommendations are made by the researchers.